International perspectives on Cross-Border working - Wakely, Richard (Irish Journal of Arts Management and Cultural Policy, 2019)
This paper provides an international perspective on cross-border working and reflects on the policy frameworks which promote cross-border working through the lens of the Belfast International Arts Festival. It suggests that Brexit will impact artist mobility, funding, and market competition in the arts and proposes that the most urgent issue is the potential of Brexit to dimantle the complex and multi-layered notions of identity in Northern Ireland and how we articulate our common European heritage.